Historical European Martial Art a crossroad between academic research, martial heritage re-creation and martial sport practices - Daniel Jaquet; Claus Frederik Sørensen; Fabrice Cognot (Bern Open Publishing, 2015)
Historical European martial arts (HEMA) have to be considered an important part of our common European cultural heritage. Studies within this field of research have the potential to enlighten the puzzle posed by past societies, for example in the field of history, history of science and technology, or fields related to material culture. The military aspects of history are still to be considered among the most popular themes of modern times, generating huge public interest. In the last few decades, serious HEMA study groups have started appearing all over the world - focusing on re-creating a lost martial art. The terminology "Historical European Martial Arts" therefore also refers to modem-day practices of ancient martial arts. Many of these groups focus on a "hands-on" approach, thus bringing practical experience and observation to enlighten their interpretation of the source material. However, most of the time, they do not establish inquiries based on scientific research, nor do they follow methodologies that allow for a critical analysis of the findings or observations. This paper will therefore propose and discuss, ideas on how to bridge the gap between enthusiasts and scholars; since their embodied knowledge, acquired by practice, is of tremendous value for scientific inquiries and scientific experimentation. It will also address HEMA practices in the context of modern day acceptance of experimental (or experiential) processes and their value for research purposes and restoration of an historical praxis. The goal is therefore to sketch relevant methodological and theoretical elements, suitable for a multidisciplinary approach, to HEMA, where the "H" for "historical" matters.